A construção de tipos de pessoas vistas a partir de bancos de dados: o caso da adolescência vulnerável - Lima, Juliana Meirelles de (2015)
This dissertation aims to investigate the discursive dimension of scientific databases. We understand that these tools are discursive practices and not merely repositories of scientific literature. Whilst the way in which articles are added to databases broadens the access researchers have to information, it also restricts the choice of articles available for access and the order in which they are accessed. Therefore, as search tools, databases have an impact on scientific practice. We have followed the argumentation presented by Hacking (1999; 2001; 2007) in order to investigate how the discursive dimension of scientific databases makes up kinds of people, more specifically, we attempt to ascertain the role databases play in determining the concept of vulnerable adolescents. We studied the history behind the use and crystallization of the notion of vulnerability as an organizing concept in the various areas of knowledge and more specifically in Psychology. To this intent, we gathered quantitative information on periodicals from the CAPES portal through a software developed exclusively for this purpose. Subsequently, we gathered information on publications from the PsycINFO database, analyzing discursively the vulnerability and vulnerable adolescents versions performed in publications from subfields of Psychology. Lastly, we focused on publications from the SciELO and BVS databases indexed by Qualis Psychology, evaluating the association between vulnerability and adolescence in national scientific publications in Brazil